Method for deeply decalcifying battery-grade sodium carbonate
Through ion exchange method and resin treatment technology, the calcium impurities in industrial sodium carbonate are deeply removed, which solves the problem of difficult reduction of calcium ion concentration in the prior art, realizes the production of battery-grade sodium carbonate, and reduces process complexity and maintenance costs.
Patent Information
- Application Number
- CN202411900324.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to remove the depth of calcium impurities in industrial sodium carbonate to below 5-10 ppm, which cannot meet the requirements of raw materials for sodium batteries. At the same time, the maintenance cost of reverse osmosis membrane is high and the treatment process is prone to clogging.
The ion exchange method is used to convert sodium chloride to sodium carbonate. The calcium ion concentration in sodium carbonate is gradually reduced by the treatment of calcium removal resin and carbonic acid resin, and finally the battery-grade sodium carbonate is obtained through recrystallization.
The calcium ion concentration in sodium carbonate is successfully reduced to less than 5ppm, meeting the requirements of battery-grade materials, while avoiding the generation of large amounts of wastewater, reducing process complexity and maintenance costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new battery materials and relates to a method for deep decalcification of battery-grade sodium carbonate. Background Art
[0002] Battery-grade sodium carbonate is used to synthesize mobile battery-grade sodium fluoride, but as a sodium battery material, metal ions are required to be at the ppm level. The calcium impurity in industrial sodium carbonate is about 200-300ppm. The existing mature technology can purify the calcium of industrial sodium carbonate to 50-60ppm, and the deep decalcification of industrial sodium carbonate to below 5-10ppm can meet the raw material requirements for sodium batteries.
[0003] Chinese patent document CN201710479120.8 discloses a method for refining industrial-grade sodium carbonate to remove trace calcium. In this method, a raw sodium carbonate solution is mixed with a refining agent in a crystallization module to generate a suspension containing calcium carbonate crystals, which is then sent to an ultrafiltration membrane module through a pipeline to obtain a concentrated solution and a purified solution. 2+ The content is reduced to below 5ppm. This industrial sodium carbonate deep decalcification method solves the problem of sodium carbonate decalcification without generating a large amount of wastewater. However, there are the following disadvantages: the deep decalcification process of sodium carbonate is relatively complicated, and the decalcification process uses a reverse osmosis membrane. The maintenance cost of the membrane is high, and the membrane is easily blocked during the treatment process.
[0004] Chinese patent document CN117756141A discloses a system and method for preparing industrial sodium carbonate refined liquid, specifically disclosing that the industrial sodium carbonate refined liquid preparation system includes: a preparation tank for dissolving industrial sodium carbonate; a feeding mechanism, the discharge port of the feeding mechanism is connected to the feed port of the preparation tank; an automatic pH regulator, the automatic pH regulator is arranged in the preparation tank, and the feeding mechanism is connected to the automatic pH regulator; a filtering mechanism, the feed port of the filtering mechanism is connected to the discharge port of the preparation tank; an adsorption mechanism, the feed port of the adsorption mechanism is connected to the discharge port of the filtering mechanism. In this invention, industrial sodium carbonate is transported to the preparation tank by the feeding mechanism to dissolve into an industrial sodium carbonate solution, and then the pH value in the preparation tank is adjusted to form a precipitate in part of the impurities in the industrial sodium carbonate solution, the precipitate is filtered out by the filtering mechanism, and then the industrial sodium carbonate solution is impurity-removed by the adsorption mechanism. The advantages are simple process, low cost of industrial sodium carbonate purification, and mature process. However, there are the following disadvantages: this process can only purify calcium impurities in industrial sodium carbonate to 50-60ppm, and cannot further reduce the calcium ions in the sodium carbonate. Summary of the invention
[0005] The invention solves the problem that deep decalcification of sodium carbonate, a raw material for synthesizing battery-grade sodium fluoride, is difficult, and the calcium ions in the sodium carbonate are removed to 5-10 ppm, so that the sodium carbonate raw material can reach battery-grade material.
[0006] The technical solution adopted by the present invention to achieve its purpose is as follows:
[0007] A method for deep decalcification of battery-grade sodium carbonate, characterized in that it comprises the following steps:
[0008] S1. Prepare a solution of industrial sodium chloride with a mass concentration of 20% to 25%, and obtain a pure sodium chloride solution after refining and filtration;
[0009] S2. The calcium removal resin is pretreated and converted into a sodium type resin for treatment, and then the pure sodium chloride solution obtained in step S1 is passed through the sodium type resin at a treatment flow rate of 1Bv / h to 2Bv / h until the calcium ion concentration in the pure sodium chloride solution is less than 1ppm to obtain a low-calcium sodium chloride solution;
[0010] S3. Prepared with electronic grade ammonium carbonate finished product with a mass concentration of 20% to 30% solution, exchange flow 2Bv / h ~ 4Bv / h, after resin treatment to obtain carbonate resin;
[0011] S4. The low-calcium sodium chloride solution obtained in step S2 is passed through the carbonate-type resin obtained in step S3, with a treatment flow rate of 0.5Bv / h to 1Bv / h to obtain a low-calcium sodium carbonate solution having a mass concentration of 10% to 18%;
[0012] S5. Recrystallize the low-calcium sodium carbonate solution obtained in step S4 to obtain battery-grade sodium carbonate solid.
[0013] Furthermore, the concentration of calcium ions in the electronic grade ammonium carbonate solution is less than 5 ppm.
[0014] Furthermore, the refined filtration in step S1 is to filter out insoluble solid particles, and the pore size of the filter element of the filtration device is less than 5 μm.
[0015] Furthermore, the calcium removal resin in step S2 is a macroporous cationic chelating resin calcium removal type resin (an extremely durable macroporous resin in which aminomethylphosphonic acid groups are connected to polystyrene copolymers).
[0016] Furthermore, in step S2, the calcium removal resin is converted into a sodium type resin by pretreatment as follows:
[0017] First, use 5% to 8% hydrochloric acid, which is 3 times the volume of the resin, at a flow rate of 3Bv / h to backwash the resin, circulate for 4 hours, and detect the calcium and iron ions in the backwash liquid. If the calcium and iron ions in the backwash liquid are greater than 1ppm, replace the hydrochloric acid for washing and repeat the above steps. The calcium and iron ions in the backwash liquid are detected to be less than 1ppm. Drain the hydrochloric acid from the resin and rinse it with water to a pH value above 4. Then, convert the sodium-type resin with 5% analytical pure sodium chloride solution, which is 3 times the volume of the resin, at a circulation flow rate of 2Bv / h for 4 hours. After the transformation, drain the liquid in the resin column and rinse it with deionized water at a flow rate of 3Bv / h for 1 hour. The resin pretreatment is completed.
[0018] Further, the preparation of the carbonate resin in step S3 is as follows:
[0019] The first step: using electronic grade ammonium carbonate finished product to prepare a solution with a mass concentration of 20% to 30%;
[0020] Step 2: The strong alkaline quaternary ammonium anion resin is rinsed with deionized water at a flow rate of 3 Bv / h for 1 hour, and the resin pretreatment is completed;
[0021] Step 3: Circulate the prepared ammonium carbonate solution in the resin column for 4 to 6 hours at a flow rate of 2 Bv / h to 4 Bv / h, which is 5 times the volume of the resin, for transformation (transformation principle: RN(CH3)3OH+CO3 2- →RN(CH3)3-CO3+OH - ), the resin is transformed into carbonate;
[0022] Step 4: Drain the ammonium carbonate solution remaining in the resin column after exchange, add deionized water to rinse at a flow rate of 3Bv / h for 1 hour, and the resin pretreatment is completed. At this time, the resin adsorption of carbonate ions reaches saturation.
[0023] Further, in step S5, the recrystallization operation is:
[0024] Step 1, concentrating the low-calcium sodium carbonate solution obtained by treatment at a temperature above 90° C., evaporating and concentrating the sodium carbonate concentration from 10% to 18%, evaporating 80% of the original solution weight, obtaining a sodium carbonate crystal mixed solution, cooling it to room temperature, and centrifuging to separate the sodium carbonate crystals;
[0025] Step 2, then adding the obtained sodium carbonate crystals into deionized water to prepare a 30% sodium carbonate solution, evaporating and concentrating at above 90° C., evaporating 60% of the solution weight, cooling to room temperature, and centrifuging;
[0026] The sodium carbonate crystals obtained in step 2 are further prepared into a 30% saturated solution, and step 2 is repeated, followed by centrifugation to obtain battery-grade sodium carbonate crystals.
[0027] The beneficial effects of the present invention are:
[0028] The invention adopts an ion exchange method to convert sodium chloride into sodium carbonate, synthesize low-calcium sodium carbonate, and achieve deep decalcification. The calcium content of the final battery-grade sodium carbonate crystals is less than 5ppm, and the chlorine content is less than 100ppm.
[0029] Principle of chloride conversion to carbonate ion:
[0030] First, sodium chloride is used to remove calcium: 20% to 25% sodium chloride solution is passed through the resin bed at a flow rate of 1Bv / H to 2Bv / H to obtain a low-calcium sodium chloride solution. The exchange principle is: RM (M represents other metal ions) + n Na + =R-Na+M n+ .
[0031] Next, chloride ions are exchanged for carbonate:
[0032] 0.5Bv / H~1Bv / H of low calcium sodium chloride solution enters the carbonate resin. At this time, the carbonate resin is saturated with adsorption and chloride ions can replace carbonate ions in a dynamic equilibrium. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should belong to the scope of protection of the present invention.
[0034] Example 1
[0035] After many experiments, the sodium carbonate deep decalcification technology first treats industrial-grade sodium chloride with ion exchange to obtain low-calcium sodium chloride (<1ppm); then the ion exchange method is used to convert the resin into a carbonate-type resin using a low-calcium ammonium carbonate solution (<5ppm); then the low-calcium sodium chloride is exchanged with the carbonate-type resin to obtain a low-calcium sodium carbonate solution, which is then concentrated, crystallized, and dried into battery-grade sodium carbonate.
[0036] The specific process is:
[0037] S1. First, prepare a 20% to 25% solution of industrial sodium chloride, refine and filter, filter out insoluble solid particles, and use a filter element with a pore size of less than 5 μm to obtain a pure sodium chloride solution;
[0038] S2. The calcium removal resin is converted into sodium type resin after pretreatment. The reaction mechanism is: R1-M (M represents other metal ions) + n Na + =R-Na+M n+. The processing flow rate is 1Bv / h~2Bv / h. The sodium chloride solution with a mass concentration of 20%~25% is treated by sodium type resin, and the calcium ions are removed to below 1ppm. After refined filtration, a low-calcium sodium chloride solution is obtained;
[0039] S3. Prepare a 20% to 30% mass concentration solution with electronic grade ammonium carbonate finished product, and obtain carbonate resin after resin treatment. The reaction mechanism is: R2-Y (Y represents anion) + X CO3 2- =R2-CO3+Y X- The exchange flow rate is 2Bv / h to 4Bv / h, and the carbonate type resin is obtained after treatment.
[0040] S4. The low calcium sodium chloride solution obtained in step S2 is treated with the carbonate resin obtained in step S3. The reaction mechanism is: R2-CO3+Na + CL - =R2-CL+Na2CO3. The flow rate of the treatment process is: 0.5Bv / h~1Bv / h. After treatment, a low-calcium sodium carbonate solution is obtained, and the mass concentration of the sodium carbonate solution is 10%~18%;
[0041] S5. A sodium carbonate solution with a mass concentration of 10% to 18% is recrystallized (washed and filtered) to obtain a low-calcium sodium carbonate solid, i.e., a battery-grade sodium carbonate solid.
[0042] In step S2, the calcium removal resin is converted into a sodium type resin by pretreatment as follows:
[0043] First, use 5% to 8% hydrochloric acid, which is 3 times the volume of the resin, at a flow rate of 3Bv / h to backwash the resin, circulate for 4 hours, and detect the calcium and iron ions in the backwash liquid. If the calcium and iron ions in the backwash liquid are greater than 1ppm, replace the hydrochloric acid for washing and repeat the above steps. The calcium and iron ions in the backwash liquid are detected to be less than 1ppm. Drain the hydrochloric acid from the resin and rinse it with water to a pH value above 4. Then, convert the sodium-type resin with 5% analytical pure sodium chloride solution, which is 3 times the volume of the resin, at a circulation flow rate of 2Bv / h for 4 hours. After the transformation, drain the liquid in the resin column and rinse it with deionized water at a flow rate of 3Bv / h for 1 hour. The resin pretreatment is completed.
[0044] The preparation of the carbonate resin in step S3 is as follows:
[0045] The first step: using electronic grade ammonium carbonate finished product to prepare a solution with a mass concentration of 20% to 30%;
[0046] Step 2: The strong alkaline quaternary ammonium anion resin is rinsed with deionized water at a flow rate of 3 Bv / h for 1 hour, and the resin pretreatment is completed;
[0047] Step 3: Circulate the prepared ammonium carbonate solution in the resin column for 4 to 6 hours at a flow rate of 2 Bv / h to 4 Bv / h, which is 5 times the volume of the resin, for transformation (transformation principle: RN(CH3)3OH+CO3 2- →RN(CH3)3-CO3+OH - ), the resin is transformed into carbonate;
[0048] Step 4: Drain the ammonium carbonate solution remaining in the resin column after exchange, add deionized water to rinse at a flow rate of 3Bv / h for 1 hour, and the resin pretreatment is completed. At this time, the resin adsorption of carbonate ions reaches saturation.
[0049] In step S5, the recrystallization operation is:
[0050] Step 1, concentrating the low-calcium sodium carbonate solution obtained by treatment at a temperature above 90° C., evaporating and concentrating the sodium carbonate concentration from 10% to 18%, evaporating 80% of the original solution weight, obtaining a sodium carbonate crystal mixed solution, cooling it to room temperature, and centrifuging to separate the sodium carbonate crystals;
[0051] Step 2, then adding the obtained sodium carbonate crystals into deionized water to prepare a 30% sodium carbonate solution, evaporating and concentrating at above 90° C., evaporating 60% of the solution weight, cooling to room temperature, and centrifuging;
[0052] The sodium carbonate crystals obtained in step 2 are further prepared into a 30% saturated solution, and step 2 is repeated, followed by centrifugation to obtain battery-grade sodium carbonate crystals.
[0053] The battery sodium carbonate content is more than 99%, the calcium ion is less than 5ppm, the chloride ion is less than 100ppm, and the ammonium ion is less than 100ppm (in the sodium carbonate concentration process, ammonia is removed under alkaline conditions), meeting the battery-grade sodium carbonate index requirements.
Claims
1. A method for deep decalcification of battery-grade sodium carbonate, characterized in that: The following steps are involved: S1. Prepare a solution of industrial sodium chloride with a mass concentration of 20% to 25%, and obtain a pure sodium chloride solution after refining and filtration; S2. The calcium removal resin is pretreated and converted into a sodium type resin for treatment, and then the pure sodium chloride solution obtained in step S1 is passed through the sodium type resin at a treatment flow rate of 1Bv / h to 2Bv / h until the calcium ion concentration in the pure sodium chloride solution is less than 1ppm to obtain a low-calcium sodium chloride solution; S3. Prepared with electronic grade ammonium carbonate finished product with a mass concentration of 20% to 30% solution, exchange flow 2Bv / h ~ 4Bv / h, after resin treatment to obtain carbonate resin; S4. The low-calcium sodium chloride solution obtained in step S2 is passed through the carbonate-type resin obtained in step S3, with a treatment flow rate of 0.5Bv / h to 1Bv / h to obtain a low-calcium sodium carbonate solution having a mass concentration of 10% to 18%; S5. Recrystallize the low-calcium sodium carbonate solution obtained in step S4 to obtain battery-grade sodium carbonate solid.
2. A method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that, The concentration of calcium ions in electronic grade ammonium carbonate solution is less than 5ppm.
3. A method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that: The refined filtration in step S1 is to filter out insoluble solid particles, and the pore size of the filter element of the filtration device is less than 5 μm.
4. A method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that: The calcium removal resin in step S2 is a macroporous cationic chelating resin calcium removal type resin.
5. A method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that: In step S2, the calcium removal resin is converted into a sodium type resin by pretreatment as follows: First, use 5% to 8% hydrochloric acid, which is 3 times the volume of the resin, at a flow rate of 3Bv / h to backwash the resin, circulate for 4 hours, and detect the calcium and iron ions in the backwash liquid. If the calcium and iron ions in the backwash liquid are greater than 1ppm, replace the hydrochloric acid for washing and repeat the above steps. The calcium and iron ions in the backwash liquid are detected to be less than 1ppm. Drain the hydrochloric acid from the resin and rinse it with water to a pH value above 4. Then, convert the sodium-type resin with 5% analytical pure sodium chloride solution, which is 3 times the volume of the resin, at a circulation flow rate of 2Bv / h for 4 hours. After the transformation, drain the liquid in the resin column and rinse it with deionized water at a flow rate of 3Bv / h for 1 hour. The resin pretreatment is completed.
6. The method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that: The preparation of the carbonate type resin in step S3 is as follows: The first step: using electronic grade ammonium carbonate finished product to prepare a solution with a mass concentration of 20% to 30%; Step 2: The strong alkaline quaternary ammonium anion resin is rinsed with deionized water at a flow rate of 3 Bv / h for 1 hour, and the resin pretreatment is completed; Step 3: Circulate the prepared ammonium carbonate solution in the resin column for 4 to 6 hours at a flow rate of 2Bv / h to 4Bv / h, which is 5 times the volume of the resin, and the resin is transformed into carbonate; Step 4: Drain the ammonium carbonate solution remaining in the resin column after exchange, add deionized water to rinse at a flow rate of 3Bv / h for 1 hour, and the resin pretreatment is completed. At this time, the resin adsorption of carbonate ions reaches saturation.
7. The method for deep decalcification of battery-grade sodium carbonate according to claim 1, characterized in that: In step S5, the recrystallization operation is: Step 1, concentrating the low-calcium sodium carbonate solution obtained by treatment at a temperature above 90° C., evaporating and concentrating the sodium carbonate concentration from 10% to 18%, evaporating 80% of the original solution weight, obtaining a sodium carbonate crystal mixed solution, cooling it to room temperature, and centrifuging to separate the sodium carbonate crystals; Step 2, then adding the obtained sodium carbonate crystals into deionized water to prepare a 30% sodium carbonate solution, evaporating and concentrating at above 90° C., evaporating 60% of the solution weight, cooling to room temperature, and centrifuging; The sodium carbonate crystals obtained in step 2 are further prepared into a 30% saturated solution, and step 2 is repeated, followed by centrifugation to obtain battery-grade sodium carbonate crystals.
Citation Information
Patent Citations
Method for removing trace calcium in sodium carbonate refining
CN109110786A
Industrial sodium carbonate refined liquid preparation system and method
CN117756141A
Method for preparing cesium carbonate by ion exchange method
CN103241750A
Sodium carbonate purification and decontamination system and method
CN108069445A
Resourceful treatment process of industrial high-concentration brine
CN111762847A